1989
DOI: 10.1159/000138525
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Effects of Extraluminally-Applied Oxyhemoglobin and Endothelial Removal on Vasodilator Responses in Isolated, Perfused Canine Basilar Arteries

Abstract: The effects of oxyhemoglobin (oxyHb) and removal of the endothelium have been measured in isolated, perfused canine basilar arteries treated with intraluminal vasodilator drugs. In preparations with an intact endothelium, acetylcholine (ACh) produces a biphasic response, where a small vasodilation precedes a vasoconstriction. Calcium ionophore A23187 and thimerosal induce a vasodilation at low doses and a biphasic response at high doses. Sodium nitroprusside (SNP) evokes only a vasodilation. Extraluminally app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Methemoglobin was much less potent in scavenging NO (Martin et al, 1985b). In isolated, perfused rabbit basilar and dog femoral arteries, it was noted that extraluminal application of oxyHb interfered with the relaxation mediated by NO liberated from the endothelium, although the extent was less than that induced by intraluminal application (Hongo et al, 1988;Toda et al, 1988;Tsuji et al, 1989). The difference in vasoconstrictions in response to oxyHb and L-NA in vivo would be due to non-NO compounds such as vasoconstrictor prostanoids (Toda et al, 1980(Toda et al, , 1991aOkamoto et al, 1984;Fujiwara et al, 1984), free radicals, such as superoxide anions (Katusic and Vanhoutte, 1989) and hydroxyl radicals (Steele et al, 1991), endothelin-1 (Cooks et al, 1991Matsumura et al, 1991;Itoh et al, 1994), etc.…”
Section: A Cerebral Vasospasm After Subarachnoid Hemorrhagementioning
confidence: 99%
“…Methemoglobin was much less potent in scavenging NO (Martin et al, 1985b). In isolated, perfused rabbit basilar and dog femoral arteries, it was noted that extraluminal application of oxyHb interfered with the relaxation mediated by NO liberated from the endothelium, although the extent was less than that induced by intraluminal application (Hongo et al, 1988;Toda et al, 1988;Tsuji et al, 1989). The difference in vasoconstrictions in response to oxyHb and L-NA in vivo would be due to non-NO compounds such as vasoconstrictor prostanoids (Toda et al, 1980(Toda et al, , 1991aOkamoto et al, 1984;Fujiwara et al, 1984), free radicals, such as superoxide anions (Katusic and Vanhoutte, 1989) and hydroxyl radicals (Steele et al, 1991), endothelin-1 (Cooks et al, 1991Matsumura et al, 1991;Itoh et al, 1994), etc.…”
Section: A Cerebral Vasospasm After Subarachnoid Hemorrhagementioning
confidence: 99%
“…Recent studies have excluded or supported the following mechanisms: formation of oxygen radicals, 24,28 release of free radicals and initiation of lipid peroxidation, 3,47 release of eicosanoids, 33 development of proliferative arteriopathy, 43 and release of endothelin-1. 40,45 Other mechanisms, such as scavenging of endotheliumderived relaxing factor (EDRF)-nitric oxide (NO) 11,50 or damage to adventitial nerves, 16,20,42 remain under investigation.…”
Section: Pathophysiological Mechanisms Of Vasospasmmentioning
confidence: 99%
“…However, deoxyhemoglobin, as oxyhemoglobin, also scavenges NO 19,22 in a reaction that produces a stable nitrosylhemoglobin. 19,53 Thus, both hemoglobins eliminate the action of this vasodilatory agent, 11,19,22,50 and vasospasm could be produced by the unopposed action of constricting agents 39,51 like endothelin-1. 40,45 The existence of such a mechanism is further supported by the loss of vasodilatory properties of the vessel wall 15,35 with preservation of its vasoconstrictive abilities.…”
Section: Pathophysiological Mechanisms Of Vasospasmmentioning
confidence: 99%
“…In addition, it was reported that hemoglobin binding of NO inhibited endotheliumdependent relaxation in the cerebral artery. 43,44 In smooth muscle cells, soluble guanylate cyclase or guanosine monophosphate, which is necessary for the relaxation response, was reduced in the canine basilar artery after SAH. 45,46 Thus, scavenging of NO or decreased response of smooth muscle to NO may also result in impaired endothelium-dependent relaxation.…”
mentioning
confidence: 99%